Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Semangat Kerja Karyawan Divisi Jasa Pengamanan PT Cipta Esavira Sejahtera - Agung Baktiar Ramdhani; Mei Retno Adiwati (Universitas Batanghari Jambi, 2023)
Increasing employee morale is an important factor so company can achieves their goals. This study aims to describe and analyze the influence of the work environments also work discipline on the morale of employees of the Security Services Division of PT. Cipta Esavira Sejahtera. The data used is primary data, namely data collected through questionnaire distributed to employees of the Security Services Division of PT. Cipta Esavira Sejahtera which consisted of 42 employees and the sample used was 42 respondents. The Likert scale is used as a measurement. The sampling technique using an saturated sampling techniques. Meanwhile, the analysis using Partial Least Square (PLS). The result of this study are: 1.) The work environment affects the morale of employees; 2.) Work discipline affects the morale of employees.